2004
DOI: 10.1079/phn2003594
|View full text |Cite
|
Sign up to set email alerts
|

Promotions to increase lower-fat food choices among students in secondary schools: description and outcomes of TACOS (Trying Alternative Cafeteria Options in Schools)

Abstract: Objectives: (1) To describe promotional activities, particularly student-led, targeting lower-fat à la carte foods that were conducted in secondary schools; and (2) to describe the relationships between the number and duration of total promotional activities for lower-fat à la carte foods and cafeteria sales of such foods over two years. Design: Promotional activities were implemented in schools that were randomised to the intervention condition of a larger, two-year, school-based, randomised, controlled nutri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 30 publications
0
25
0
3
Order By: Relevance
“…However, other studies have found that nutritional knowledge is not enough 10 and that hands-on approaches can be more effective. 23 Rather than one specific activity, it is likely that the combination of field trips, workshops, shopping and cooking, and other activitiesappealing to a variety of learning styles-contributed to any observed changes While our findings are based on a small population, they suggest that a more holistic curriculum encompassing practical skills as well as education about food and exposure to local food sources can have a positive impact on food attitudes and behaviors.…”
Section: Wrap-upmentioning
confidence: 71%
See 2 more Smart Citations
“…However, other studies have found that nutritional knowledge is not enough 10 and that hands-on approaches can be more effective. 23 Rather than one specific activity, it is likely that the combination of field trips, workshops, shopping and cooking, and other activitiesappealing to a variety of learning styles-contributed to any observed changes While our findings are based on a small population, they suggest that a more holistic curriculum encompassing practical skills as well as education about food and exposure to local food sources can have a positive impact on food attitudes and behaviors.…”
Section: Wrap-upmentioning
confidence: 71%
“…This focus on local, sustainable food systems belongs to a growing national trend of interest in organic, local, and sustainable foods. While other studies have shown that education about food (rather than Downloaded by [Nova Southeastern University] at 16:09 27 December 2014 nutrition), experiential learning, and acquisition of concrete skills such as cooking positively impact children's food choices, 11,12,16,23 we posit expanding the spectrum of nutrition education to include exposure to local food sources.…”
Section: Implications For Research and Practicementioning
confidence: 93%
See 1 more Smart Citation
“…The involvement and support of the school community and parents are also critical for success. Promising strategies to promote consumption of new foods include taste testing for parents and students (26)(27)(28) , signs on the food line (26,28) , parent meetings (23) and media campaigns (26,28)) . The IOM report also recommended training on the new meal patterns for school food service staff for successful implementation.…”
Section: Discussionmentioning
confidence: 99%
“…School-based programs are efficient in their ability to reach large numbers of children. Programs that increase access to nutritious foods at school, 34 offer promotional activities for healthy snacks 35 and reduce prices on low-fat snacks 36 are all effective in increasing sales of these food items. Likewise, providing students with a free piece of fruit at school is an effective strategy to increase students' fruit consumption 37,38 and school breakfast programs contribute to adequate nutrient intakes of students.…”
Section: Discussionmentioning
confidence: 99%